Negotiating the Lack of Intimacy in Assisted Living: Resident Desires, Barriers, and Strategies. (January 2020) - Bender, Alexis A.; Burgess, Elisabeth O.; Barmon, Christina
Despite continuity in the desire for sex and partnership, many older adults experience a lack of intimacy in late life. The use of assisted living is a complicating factor for understanding issues of partnership, sex, and intimacy for older adults. Using in-depth interviews with 23 assisted living residents and grounded theory methods, we examined how residents negotiate a lack of intimacy in assisted living. The process of negotiation entailed three factors: desire, barriers, and strategies. Although some residents continued to desire intimacy, there was a marked absence of dating or intimacy in our study sites. Findings highlight unique barriers to acting on desire and the strategies residents used as aligning actions between desire and barriers. This research expands previous studies of sexuality and older adults by examining the complex ways in which they balanced desire and barriers through the use of strategies within the assisted living environment.